2017
DOI: 10.18805/ijar.v0iof.9177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc supplementation on hormonal and lipid peroxidation status of peri-parturient Karan Fries cows during heat stress condition

Abstract: Present study was carried out to evaluate the effect of Zinc (Zn) supplementation on hormonal and lipid peroxidation status of peri-parturient KF (Karan Fries) cows during heat stress. Cows were grouped as C (6), T1 (6) and T2 (6). C was fed basal diet alone; however T1 and T2 were fed with 80 ppm and 120 ppm Zn, respectively along with basal diet from 45 days prepartum to 45 days postpartum. It was found that Zn level was significantly (P<0.05) higher in supplemented group than control. Plasma cortisol was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…The results of the present study disagree with the previously study carried out by Alimohamady et al(2019) who observed that there were no significant differences of serum Zn concentrations between groups supplemented by organic Zn (Zn-methionine and Zn-proteinate supplementation) and inorganic Zn(Zn-sulfate) compared to control group in lambs under normal conditions. In agreement with the data published by Patel et al(2018) who observed that serum Zn level was significantly higher in supplemented groups were fed with 80 ppm and 120 ppm Zn compared to control group in Karan Fries cows during heat stress. concerning the level of ALT in serum is illustrated in (Table 4).…”
Section: Results and Discusstionssupporting
confidence: 92%
“…The results of the present study disagree with the previously study carried out by Alimohamady et al(2019) who observed that there were no significant differences of serum Zn concentrations between groups supplemented by organic Zn (Zn-methionine and Zn-proteinate supplementation) and inorganic Zn(Zn-sulfate) compared to control group in lambs under normal conditions. In agreement with the data published by Patel et al(2018) who observed that serum Zn level was significantly higher in supplemented groups were fed with 80 ppm and 120 ppm Zn compared to control group in Karan Fries cows during heat stress. concerning the level of ALT in serum is illustrated in (Table 4).…”
Section: Results and Discusstionssupporting
confidence: 92%
“…The SOD differed significantly (P<0.01) in the T1 and T2 groups compared to the control group. Similar findings were also reported by Patel et al (2021) and Nagalakshmi et al (2009) on zinc supplementation. The increase in SOD activity after zinc supplementation might be because zinc is an intrinsic constituent of superoxide dismutase, a major scavenger of free radicals present in the cytoplasm of many types of cells (Spears and W eiss, 2008).…”
Section: Superoxide Dismutasesupporting
confidence: 90%
“…Highly significant (P<0.01) increase was noticed in the T2 group followed by the T1 group as compared to the T0 group on TAC. The findings in the present study are in accordance with Shen et al (2021) and Patel et al (2021). In contrast, Ulutas et al (2020) reported no significant change in antioxidant activity after zinc supplementation.…”
Section: Total Antioxidant Capacitysupporting
confidence: 89%
“…Suraj [ 15 ] also found a significant (p<0.01) decrease in cortisol levels in KF heifers supplemented with 2.5% prilled fat. Patel [ 31 ] found a significant (p<0.05) decrease in cortisol content in pregnant KF cows supplemented with 80 and 120 ppm zinc. Finally, according to Broadway et al .…”
Section: Discussionmentioning
confidence: 99%